THE INFLUENCE OF RAW MATERIAL SUPPLIES, PRODUCTION PROCESS AND EQUIPMENT MAINTENANCE ON PRODUCT QUALITY IN SMALL RED BRICK INDUSTRIES IN CILEGON CITY - Aprida, Wahdatul; Mukhsin, Moh; Satyanegara, Diqbal (Universitas Nusa Cendana, 2025)
The aim of this research is to determine the impact of raw material supplies, production processes and equipment maintenance on product quality in the Small Red Brick Industry in Cilegon City, whether the influence is partial or simultaneous. The used method is quantitative and associative research, with a sample of 77 respondents. Data collection using questionnaires and the results were processed using the SPSS 26 program. The research results showed that raw material supplies, production processes and equipment maintenance had an impact on product quality simultaneously. Partially, raw material supplies have an impact on product quality, the production process has no impact on product quality. And equipment maintenance has an impact on product quality. Keywords: Raw Material Supplies; Production Process; Equipment Maintenance